Co2 Removal Using Polyvinylidene Fluoride Mixed Matrix Membrane In Membrane Gas Absorption - Ahmad, Nor Aini (2019)
Carbon dioxide (CO2) removal technology is important in the purification of energy source such as biogas. Among the CO2 removal techniques, membrane gas absorption (MGA) can be used to separate CO2 at low pressure. MGA integrates the advantages of membrane and chemical absorption process in a single unit. However, membrane wetting in the long operation can induce the increment of mass transfer resistance even using hydrophobic membranes. Polyvinylidene fluoride (PVDF) is the commonly used membrane in MGA, but PVDF defluorination in amine solutions was postulated to cause membrane wetting. In this research, poly[2,2’-(m-phenylene)-5,5’-dibenzimidazole (PBI) with the great chemical resistance and thermal stability was blended into PVDF membrane to enhance the physical and chemical properties membrane. Besides that, SAPO-34 zeolite with CO2 absorption affinity was incorporated into PVDF membrane to improve CO2 absorption. PVDF membrane incorporated with SAPO-34 zeolite was hydrophobically modified using silane. Hydrogen bonding in the polymer blend due to donor (-NH-) and proton acceptor (-N=) of PBI encouraged the formation of miscibility blend. PVDF/PBI membrane with 20 wt% of PBI showed the highest CO2 flux of 3.07 x 10-4 mol/m2s. The CO2 flux of PVDF membrane increased 60 % to 4.53 x 10-4 mol/m2s when it was blended with 10 wt% of SAPO-34 zeolite. The pre-modified SAPO-34 zeolite using fluorocarbon silane retarded the formation of porous structure, resulting in a great membrane resistance for CO2 transfer. The post-modification of PVDF/SAPO-34 membrane using silane caused improvement in CO2 absorption. The significant improvement of water contact angle and liquid entry pressure resulted in the increment of overall mass transfer coefficient (Ko) to 12.46 x 10-6 m/s. Introducing humid CO2 gas into MGA system incorporated with the post-modified PVDF/SAPO-34, the CO2 permeation was significantly reduced to 10.65 x 10-6 m/s. The Ko of post-modified membrane remained similar to the overall mass transfer coefficient of non-silanated PVDF/SAPO-34 membrane. The wetting study conducting in diethanolamine (DEA) solution (2 M) showed that incorporation of zeolite reduced swelling of that PVDF/SAPO-34 membrane. However, the unfavorable interaction between fluoroalkyl and amine groups induced severe wetting of post-modified PVDF/SAPO-34 membrane by amine. Hence, PVDF/SAPO-34 hollow fiber with different SAPO-34 loadings (1, 3 and 5 wt%) were synthesized. The highest CO2 flux of 8.73 x 10-4 mol/m2s was achieved when 3 wt% of SAPO-34 zeolite was incorporated into PVDF/SAPO-34 hollow fiber. PVDF/SAPO-34 hollow fiber exhibited lower mass transfer resistance in comparison to PVDF/SAPO-34 flat sheet. The CO2 absorption flux of PVDF/SAPO-34 membrane was greatly improved of about 140 % higher than the CO2 absorption flux of the neat membrane when 2 M DEA was used as the liquid absorbent. Neat hollow fiber membrane swelled nearly 71.0 % after being wetted by amine. However the incorporation of SAPO-34 zeolite into PVDF hollow fiber membrane reduced swelling by amine, down to 47.7 %.